ARRANGEMENT OF TRADITIONAL INSTITUTIONS IN INDONESIAN LEGAL SYSTEM - Oktavani Yenny; I Wayan Atmanu Wira Pratana; I Made Halmadiningrat (TANJUNGPURA LAW JOURNAL, 2023)
AbstractThe establishment of the Majelis Desa Adat/Traditional Village Council (MDA) in Bali Province and the Majelis Dewan Adat Dayak Nasional/National Dayak Customary Council in Kalimantan (MADN) in Kalimantan Province are clear examples that the customary law community unit seriously shows its existence to accommodate the interests of members and create policies that can directly affect the customary law community unit. However, the existence of these two customary institutions does not yet have legal certainty in Indonesian legal arrangements that specifically discuss their position. As a result, the position of these customary institutions in the national realm is ambiguous due to the unclear status and position of legal products and the strength of the policies issued. The purpose of this research is to discuss the position of the customary village council in Bali Province and the national Dayak Customary Council in Kalimantan in the laws and regulations and the status of policies issued by customary institutions in Indonesian laws and regulations. The method used is normative legal research. Data sources consist of primary legal materials, secondary legal materials, and tertiary legal materials. In this research, the data is analyzed qualitatively and then presented descriptively to get a comprehensive conclusion. The results show that the MDA and the MADN have experienced significant developments ranging from institutional arrangements to legal products issued. Therefore, to provide legal certainty to the position of customary institutions and the status of legal products issued by Customary Institutions, it is necessary to explicitly regulate in Law Number 12 of 2011 as amended by Law Number 13 of 2022 concerning the Second Amendment to Law Number 12 of 2011 concerning the Formation of Legislation concerning the position of Customary Institutions and the resulting Legal Products so that there is no overlap of policies between positive law and customary law that is currently running.AbstrakPembentukan Majelis Desa Adat (MDA) di Provinsi Bali dan Majelis Dewan Adat Dayak Nasional (MADN) di Provinsi Kalimantan menjadi contoh nyata bahwa kesatuan masyarakat hukum adat secara serius menunjukan keberadaannya untuk mengakomodir kepentingan anggota dan menciptakan kebijakan-kebijakan yang dapat berpengaruh secara langsung kepada kesatuan masyarakat hukum adat. Namun, keberadaan kedua lembaga adat ini belum memiliki kepastian hukum di dalam pengaturan hukum Indonesia yang secara spesifik membahas mengenai kedudukannya. Akibatnya kedudukan lembaga adat ini di ranah nasional menjadi ambigu karena ketidakjelasan status dan posisi produk hukum maupun kekuatan dari kebijakan yang dikeluarkan. Tujuan penelitian ini untuk membahas mengenai kedudukan majelis desa adat di Provinsi Bali dan majelis adat dayak nasional di Kalimantan dalam peraturan perundang-undangan dan status kedudukan kebijakan yang dikeluarkan oleh lembaga adat pada peraturan perundang-undangan di indonesia. Metode yang dipergunakan adalah penelitian hukum normatif. Sumber data terdiri atas bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Dalam penelitian ini data dianalisis secara kualitatif yang kemudian disajikan secara deskriptif untuk mendapatkan kesimpulan yang komprehensif. Hasil penelitian menunjukkan bahwa MDA dan MADN telah mengalami perkembangan yang sangat signifikan mulai dari tata kelembagaan hingga produk hukum yang dikeluarkan. Oleh karena itu, untuk memberikan kepastian hukum terhadap kedudukan lembaga adat serta status kedudukan produk hukum yang dikeluarkan oleh lembaga adat, maka perlu adanya pengaturan secara tegas di dalam Undang-Undang Nomor 12 Tahun 2011 sebagaimana telah diubah menjadi Undang-Undang Nomor 13 Tahun 2022 tentang Perubahan kedua atas Undang-undang Nomor 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-undangan tentang Kedudukan Lembaga Adat dan Produk Hukum yang dihasilkan agar tidak terjadi tumpang tindih kebijakan antara hukum positif dengan hukum adat yang saat ini telah berjalan.